Intra-uterine undernutrition amplifies age-associated glucose intolerance in pigs via altered DNA methylation at muscle GLUT4 promoter. Issue 3 (6th June 2016) - Wang, Jun; Cao, Meng; Yang, Mei; Lin, Yan; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Feng, Bin; Li, Jian; Wu, De
Abstract: The present study aimed to investigate the effect of maternal malnutrition on offspring glucose tolerance and the epigenetic mechanisms involved. In total, twelve primiparous Landrace×Yorkshire gilts were fed rations providing either 100 % (control (CON)) or 75 % (undernutrition (UN)) nutritional requirements according to the National Research Council recommendations, throughout gestation. Muscle samples of offspring were collected at birth (dpn1), weaning (dpn28) and adulthood (dpn189). Compared with CON pigs, UN pigs showed lower serum glucose concentrations at birth, but showed higher serum glucose and insulin concentrations as well as increased area under the blood glucose curve during intravenous glucose tolerance test at dpn189 ( P <0·05). Compared with CON pigs, GLUT-4 gene and protein expressions were decreased at dpn1 and dpn189 in the muscle of UN pigs, which was accompanied by increased methylation at the GLUT4 promoter ( P <0·05). These alterations in methylation concurred with increased mRNA levels of DNA methyltransferase ( DNMT ) 1 at dpn1 and dpn28, DNMT3a at dpn189 and DNMT3b at dpn1 in UN pigs compared with CON pigs ( P <0·05). Interestingly, although the average methylation levels at the muscle GLUT4 promoter were decreased at dpn189 compared with dpn1 in pigs exposed to a poor maternal diet ( P <0·05), the methylation differences in individual CpG sites were more pronounced with age. Our results indicate that in utero undernutrition persists to silence muscle GLUT4 likely through DNA methylation during the ageing process, which may lead to the amplification of age-associated glucose intolerance.